BMW AG equity research: valuation techniques, analyses, and recommendations - Morais, Vasco Manuel da Costa (2022)
Due to the ongoing uncertainty regarding the Covid-19 pandemic, we face several challenges in forecasting the performance of BMW Group AG, thus we consider three different scenarios. To adequately value the BMW Group AG, we perform two major valuation analyses on the BMW Group AG, them being the intrinsic and the relative valuation. The first consists of a sum of the parts valuation through both a DCF and a FCFE approach, resulting in an estimated December 2022 price per share of €91.35. The second consists of trading multiples comparison and utilizes the forward-looking P/E and EV/EBITDA, and resulted in an estimated price of€58. The first estimated price is closer to the current price of BMW Group AG’s share, thus it is our target price, which yields a return of 5.32%in comparison to the current price.